Direct deposition of multi-walled carbon nanotubes onto stainless steel and YEF foils using a simple electrophoretic deposition for electrochemical capacitor electrode - Mohd Abid, Mohd Asyadi 'Azam; Talib, Elyas; Raja Seman, Raja Noor Amalina (IOP Publishing Ltd, 2019)
Metals including metal alloys have been widely used as current collector in energy storage devices. Many papers reported the direct deposition of carbon materials like multi-walled carbon nanotube (MWCNT) onto aluminum or copper or stainless steel foils. However, it is important to note that the study of YEF 50, an engineering iron alloy and high performance stainless steel SUS 310S as current collector is very limited. This manuscript discusses the usage of electrophoretic deposition technique using the MWCNT colloids in isopropyl alcohol electrolyte during the direct deposition. Other than CNT characterization using several analytical techniques, electrochemical analyses confirmed the excellent capacitive performance of MWCNT electrode with the evidence of small internal resistance. From cyclic voltammetry measurement at 1 mV s−1, a relatively high specific gravimetric capacitance of 124 F g−1 and 89 F g−1 for YEF 50 and SUS 310S, respectively were obtained. Other than the intrinsic properties of the CNTs, the excellent capacitance is attributed to the polyvinyl alcohol react as adhesivematerial between MWCNT and the surface of conductive substrate